Oxygen mass transfer impact on citric acid production by Yarrowia lipolytica from crude glycerol - Ferreira, Patrícia (2016)
Production of citric acid from crude glycerol from biodiesel industry, in batch cultures of Yarrowia lipolytica W29 was performed in a lab-scale stirred tank bioreactor in order to assess the effect of oxygen mass transfer rate in this bioprocess. An empirical correlation was proposed to describe oxygen volumetric mass transfer coefficient (kLa) as a function of operating conditions (stirring speed and specific air flow rate) and cellular density. kLa increased according with a power function with specific power input and superficial gas velocity, and slightly decreased with cellular density. The increase of initial kLa from 7 h-1 to 55 h-1 led to 7.8-fold increase of citric acid final concentration. Experiments were also performed at controlled dissolved oxygen (DO) and citric acid concentration increased with DO up to 60% of saturation. Thus, due to the simpler operation setting an optimal kLa than at controlled DO, it can be concluded that kLa is an adequate parameter for the optimization of citric acid production from crude glycerol by Y. lipolytica and to be considered in bioprocess scale-up. Our empirical correlation, considering the operating conditions and cellular density, will be a valid tool for this purpose.